The Curious Question of Exercise-Induced Pulmonary Edema - Bates, Melissa L.; Farrell, Emily T.; Eldridge, Marlowe W. (Pulmonary Medicine, 2011)
The question of whether pulmonary edema develops during exercise on land is controversial. Yet, the development of pulmonary edema during swimming and diving is well established. This paper addresses the current controversies that exist in the field of exercise-induced pulmonary edema on land and with water immersion. It also discusses the mechanisms by which pulmonary edema can develop during land exercise, swimming, and diving and the current gaps in knowledge that exist. Finally, this paper discusses how these fields can continue to advance and the areas where clinical knowledge is lacking.